The Concept and Implementation of Kaizen in an Organization (Global Journal of Management and Business Research, 2019)
For continuous improvement in an organization, Japanese philosophy Kaizen is very popular. Flawless concepts of kaizen methodology and proper implementation of tools can lead to a successful kaizen program in a company. From the reviews of various case studies, it has revealed that most of the companies have implemented kaizen efficiently and observe better performance. Besides, some companies also failed to implement kaizen due to the lacking of proper knowledge about the concepts of kaizen.
Keywords: kaizen; 5 why technique; 5s; 7 QC tools; 7 wastes; jidoka; PDCA cycle; poka-yoke